2021
DOI: 10.1002/bsd2.166
|View full text |Cite
|
Sign up to set email alerts
|

CEO characteristics and environmental disclosure of listed firms in an emerging economy: Does sustainability reporting format matter?

Abstract: The study's purpose examines chief executive officer (CEO) characteristics, sustainability reporting format, and environmental disclosure of listed firms in India. Eight hundred firm‐year observations across India's firms applied panel regression with random effect assumptions and general method of moment. The first findings show that reporting format has a positive and statistically significant association with environmental disclosure. The second findings show that CEO age and CEO tenure have an insignifican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…The standard deviation of CSR was 9.685, indicating that there are significant differences in the performance of CSR across the firms sampled in this study. The mean (median) CEO tenure was 11.449 (8), indicating that a CEO in a Saudi firm has an average tenure of 11 years. Table 3 also shows that the percentage of CEOs of Saudi nationality is 77.67%, while the percentage of other nationalities is 22.33%.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard deviation of CSR was 9.685, indicating that there are significant differences in the performance of CSR across the firms sampled in this study. The mean (median) CEO tenure was 11.449 (8), indicating that a CEO in a Saudi firm has an average tenure of 11 years. Table 3 also shows that the percentage of CEOs of Saudi nationality is 77.67%, while the percentage of other nationalities is 22.33%.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…However, CSR reporting continues to vary greatly across firms, which has prompted several investigations into the determinants of a firm's CSR commitment. Previous studies have shown that the CEO of a firm can significantly influence CSR reporting; thus, the incentives and characteristics of the CEO can explain the differences in the reporting of CSR activities across firms [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Gerged (2021), Prado-Lorenzo and Garcia-Sanchez (2010), and Jizi et al (2014) emphasized the beneficial correlation between CEO duality and environmental disclosure. However, they occasionally result in a decline in environmental disclosure (Oware and Awunyo-Vitor, 2021;Hassan et al, 2020;Jizi et al, 2014). More powerful CEOs advocate for social and environmental transparency to be considered effective and boost their tenure or salary possibilities (Jizi et al, 2014).…”
Section: Ceo Dualitymentioning
confidence: 99%
“…Within the realm of the CSR literature, researchers have predicted that factors that improve a firm's corporate social performance. These include financial slack (Boso et al, 2017; Julian & Ofori‐Dankwa, 2013), managerial attitudes (Adomako & Amankwah‐Amoah, 2021; Roxas & Coetzer, 2012), managerial characteristics (Oware & Awunyo‐Vitor, 2021; Walls & Berrone, 2017), and stakeholder pressure (Adomako & Tran, 2022; Nguyen & Adomako, 2021). In addition, the upper echelons theory suggests that top management (e.g., chief executive officers) plays an important role in the decision‐making process which ultimately affects the performance of the firm (Hambrick, 2007; Hambrick & Mason, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…These include financial slack (Boso et al, 2017;Julian & Ofori-Dankwa, 2013), managerial attitudes (Adomako & Amankwah-Amoah, 2021;Roxas & Coetzer, 2012), managerial characteristics (Oware & Awunyo-Vitor, 2021;Walls & Berrone, 2017), and stakeholder pressure (Adomako & Tran, 2022;Nguyen & Adomako, 2021).…”
mentioning
confidence: 99%